N(2)- 1-(2-Hydroxyphenyl)ethylidene -N(2)'-(1H-indol-3-ylmethylene)carbonic dihydrazide - Saharin, S.M.; Mahmood, A.A.; Robinson, W.T.; Ali, Hapipah Mohd (International Union of Crystallography, 2008)
In the crystal structure of the title compound {alternative name: 1-[1-(2-hydroxyphenyl)ethylideneamino]-3-(1H-indol-3-ylmethyleneamino)urea}, C(18)H(17)N(5)O(2), the planar indole component is twisted at an angle of 63.7 (10)degrees with respect to the rest of the molecule. This compound is one of a series being studied for biological activity. The hydroxy groups are involved in both intramolecular (O-H center dot center dot center dot N) and intermolecular (N-H center dot center dot center dot O) hydrogen bonds.